2015
DOI: 10.1007/s12928-015-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and prognosis of lesions with in-stent eccentric tissue proliferation and strong signal attenuation detected by optical coherence tomography

Abstract: There are still some patients who require repeat revascularization despite of drug-eluting stent (DES) implantation. The present study aimed to investigate the relationship between optical coherence tomography (OCT) findings and recurring target lesion revascularization (TLR) after percutaneous coronary intervention (PCI) for in-stent restenosis (ISR). We reviewed 50 patients (54 coronary lesions) who underwent PCI for ISR, which included 25 DES-ISR lesions. The PCI strategy depended on the interventionalist's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…4) Pathophysiology of restenosis specific to dialysis patients may exist. Late restenosis or calcium-phosphate metabolism 5,6) may be responsible for the poor clinical outcomes in hemodialysis patients.…”
mentioning
confidence: 99%
“…4) Pathophysiology of restenosis specific to dialysis patients may exist. Late restenosis or calcium-phosphate metabolism 5,6) may be responsible for the poor clinical outcomes in hemodialysis patients.…”
mentioning
confidence: 99%
“…Previous pathological studies reported that neointima rich in smooth muscle cells and proteoglycans, superficial foam cell accumulation, necrotic core, calcification, and organized thrombus were observed after DES placement . Similarly, clinical OCT studies of patients presenting with in‐stent restenosis have also demonstrated several types of tissues on OCT . Furthermore, the OCT appearance of in‐stent restenosis tissues after DES significantly differed between early and late restenosis phases .…”
Section: Discussionmentioning
confidence: 88%
“…9,10,15 Previous pathological studies reported that neointima rich in smooth muscle cells and proteoglycans, superficial foam cell accumulation, necrotic core, calcification, and organized thrombus were observed after DES placement. 9,10,15 Similarly, clinical OCT studies of patients presenting with in-stent restenosis have also demonstrated several types of tissues on OCT. 11,16,17 Furthermore, the OCT appearance of in-stent restenosis tissues after DES significantly differed between early and late restenosis phases. 7,8 In line with the findings of a previous study, homogeneous high-intensity signal neointima, which was frequently observed in restenotic lesions that developed within 2 years after deployment, was observed in only 4% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary intervention or percutaneous coronary intervention (PCI) is an important therapeutic method for coronary artery disease (CAD) [ 1 ], and in-stent restenosis (ISR) is the most common complication of PCI, which occurs in 3%–20% of patients undergoing coronary stent implantation [ 2 ]. ISR is a key risk factor that affects the prognosis of PCI and is a difficult problem associated with coronary intervention of CAD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%